Sustained relief of generalized dystonia despite prolonged interruption of deep brain stimulation. Issue 10 (11th February 2013) - Cheung, Tyler; Zhang, Cen; Rudolph, Joseph; Alterman, Ron L.; Tagliati, Michele
ABSTRACT Background Pallidal deep brain stimulation (DBS) is an established treatment for disabling, medication‐refractory generalized dystonia. Patients typically regress to their preoperative baseline when stimulation is discontinued. Methods Presented are case reports of 2 dystonia patients. Results Two patients with primary generalized dystonia (1 with the DYT1 mutation) who were treated successfully with bilateral pallidal DBS for periods of 18 months and 5 years retained motor benefit for several months after inadvertent interruption of stimulation. Stimulation was interrupted unilaterally for 3 and 7 months and bilaterally for 2 days and 2 months, respectively. Symptoms of dystonia returned only partially during the period of therapy interruption and rapidly and completely resolved after resuming stimulation. Conclusions We report unexpected and prolonged retention of motor benefits despite transient cessation of pallidal DBS in 2 dystonia patients. Factors that appear to differentiate these individuals are young age, short duration of disease, and chronic DBS therapy with relatively low energy of stimulation. © 2013 International Parkinson and Movement Disorder Society